2005
DOI: 10.1074/jbc.m412603200
|View full text |Cite
|
Sign up to set email alerts
|

Folding Regulates Autoprocessing of HIV-1 Protease Precursor

Abstract: Autoprocessing of HIV-1 protease (PR) precursors is a crucial step in the generation of the mature protease. Very little is known regarding the molecular mechanism and regulation of this important process in the viral life cycle. In this context we report here the first and complete residue level investigations on the structural and folding characteristics of the 17-kDa precursor TFR-PR-C nn (161 residues) of HIV-1 protease. The precursor shows autoprocessing activity indicating that the solution has a certain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 55 publications
2
28
0
1
Order By: Relevance
“…These experiments have revealed that there can be both native-like and non-native secondary structure present, the exact structure depending upon the protein and experimental conditions. For example, both native and non-native secondary structural preferences were observed in the urea-denatured state of barstar (Bhavesh et al, 2004), in the GdmCldenatured state of HIV-1 protease (Bhavesh et al, 2001;Chatterjee et al, 2005), and in the acid-denatured state of hUBF HMG box 1 (Zhang et al, 2005). In contrast, ␤-type preferences were seen in denatured apomyoglobin which is a highly helical protein (Mohana-Borges et al, 2004).…”
Section: A Superstable Core Of Gfp Characterized At Extreme Conditionsmentioning
confidence: 84%
“…These experiments have revealed that there can be both native-like and non-native secondary structure present, the exact structure depending upon the protein and experimental conditions. For example, both native and non-native secondary structural preferences were observed in the urea-denatured state of barstar (Bhavesh et al, 2004), in the GdmCldenatured state of HIV-1 protease (Bhavesh et al, 2001;Chatterjee et al, 2005), and in the acid-denatured state of hUBF HMG box 1 (Zhang et al, 2005). In contrast, ␤-type preferences were seen in denatured apomyoglobin which is a highly helical protein (Mohana-Borges et al, 2004).…”
Section: A Superstable Core Of Gfp Characterized At Extreme Conditionsmentioning
confidence: 84%
“…In this regard, sequences adjacent to the PR region have been demonstrated to influence the dimerization efficiency of the Gag-Pol precursors and proper folding of the embedded PR domains, thereby triggering PR autoprocessing (6,10,21,22,23,30,33,42). Accordingly, dimerization defects of PR mutants carrying an inactivated dimer interface were successfully compensated for when the PR was expressed as part of the Gag-Pol precursor (30).…”
Section: Discussionmentioning
confidence: 99%
“…Proper folding of the embedded homodimeric protease (PR) is an essential prerequisite for full activity following sequential autocleavage from the full-length Gag-Pol polyprotein (summarized in reference 13). Indeed, the p6* residues have been demonstrated to stabilize the PR dimer and dictate the folding propensities of PR precursors, thereby influencing the rate of PR maturation (6,10,21). Interestingly, the autoprocessing of a truncated Gag-PR precursor was clearly accelerated when the p6* sequence was deleted, leading to the proposal that the active site of the PR might be less accessible in the presence of p6* (26).…”
mentioning
confidence: 99%
“…Nuclear magnetic resonance analysis of recombinant p6* protein revealed a widely flexible structure (3,22), and its presence directly upstream of the PR is reminiscent of the propeptides flanking eukaryotic aspartic proteases and has been proven to prevent folding of the PR to its dimeric structure (6). Indeed, we could provide evidence that recombinant p6* protein is a strong competitive inhibitor of PR activity in vitro, and we proposed a model in which the carboxyl-terminal tetrapeptide of p6* following release from the Pol precursor, blocks the substrate binding cleft of the PR, thereby delaying overall processing (37).…”
mentioning
confidence: 99%